2019
DOI: 10.1093/ijnp/pyz024
|View full text |Cite
|
Sign up to set email alerts
|

The Role of DRD1 and DRD2 Receptors for Response Selection Under Varying Complexity Levels: Implications for Metacontrol Processes

Abstract: Background Highly complex tasks generally benefit from increases in cognitive control, which has been linked to dopamine. Yet, the same amount of control may actually be detrimental in tasks with low complexity so that the task-dependent allocation of cognitive control resources (also known as “metacontrol”) is key to expedient and adaptive behavior in various contexts. Methods Given that dopamine D1 and D2 receptors have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Whether the systems are more aptly defined in terms of neuroanatomical site or receptor families, this suggests that there is a persistencepromoting system and a flexibility-promoting system that together (according to their relative strength or contribution) generate cognitive control as an emerging property, which can be biased toward persistence or toward flexibility. Accordingly, genetic predispositions that impair the optimal functionality of dopaminergic processing in the persistence system (frontal pathway or D1 receptors) should lead to poor performance in tasks that rely on persistence, whereas predispositions impairing the optimal functionality of dopaminergic processing in the flexibility system (striatal pathway or D2 receptors) should lead to poor performance in tasks relying on flexibility-which is indeed what the data show (15,(26)(27)(28)(29). Culture can also play a role, as shown by findings that cultural factors that favor individualism are beneficial for performance in persistenceheavy tasks while factors that favor collectivism are beneficial for performance in flexibility-heavy tasks (15).…”
Section: From Unipolar To Bipolar Accounts Of Cognitive Control: the ...mentioning
confidence: 62%
“…Whether the systems are more aptly defined in terms of neuroanatomical site or receptor families, this suggests that there is a persistencepromoting system and a flexibility-promoting system that together (according to their relative strength or contribution) generate cognitive control as an emerging property, which can be biased toward persistence or toward flexibility. Accordingly, genetic predispositions that impair the optimal functionality of dopaminergic processing in the persistence system (frontal pathway or D1 receptors) should lead to poor performance in tasks that rely on persistence, whereas predispositions impairing the optimal functionality of dopaminergic processing in the flexibility system (striatal pathway or D2 receptors) should lead to poor performance in tasks relying on flexibility-which is indeed what the data show (15,(26)(27)(28)(29). Culture can also play a role, as shown by findings that cultural factors that favor individualism are beneficial for performance in persistenceheavy tasks while factors that favor collectivism are beneficial for performance in flexibility-heavy tasks (15).…”
Section: From Unipolar To Bipolar Accounts Of Cognitive Control: the ...mentioning
confidence: 62%
“…How might signal variability in the brain translate into metacontrol biases towards persistence or exibility? Researchers have proposed that dopamine (DA) and inter-individual differences in DA levels and/or the dynamics of these levels over time are promising candidates for linking characteristics of neural processing, like differences in neural variability, to behavior 3,47−49 and some evidence suggests that dopaminergic (or catecholamine system activity) is associated with metacontrol [50][51][52][53] .…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of the enzyme was detected in the locus coeruleus and VTA, following chronic administration of abused drugs 35–38 . The decreased level of DRD2 in the VTA might be in response to elevated DA levels as DRD2 acts as an autoinhibitory receptor protein that inhibits DA production 39,40 . Also, a recent study revealed that repeated treatment with PCP analogs elevated DRD1 and TH and reduced DRD2 protein levels in the mesolimbic dopaminergic system 5 .…”
Section: Discussionmentioning
confidence: 99%